+0  
 
+1
173
4
avatar+302 

Find the ratio in which the point(-3,k) divides the line segment joining the points (-5,-4) and (-2,3). Also find the value of k.

 

i'm getting the value of k as 5 using the formula \(\sqrt{}(x2-x1)2 +(y2-y1)2\) i hope u understood the formula it's (x2-x1)² and same with y and root sqr . but i'm getting the ratio as fraction. please solve this so i can see what mistake i made.

SARAHann  Apr 1, 2017
Sort: 

4+0 Answers

 #1
avatar+90581 
+2

You probably will not like my answe much Sara because I do not do questions like this by formula.

I can never remember formulas that I do not think I really need.  It is some weird kind of mental block  angry

 

Find the ratio in which the point(-3,k) divides the line segment joining the points (-5,-4) and (-2,3). Also find the value of k.

 

Look at the x values first

-2--5=3

-3--5=2

so the dividing point  is 2/3 of the way starting from the first end point.           The ratio is 2:3

so the k value must also be 2/3 of the way, starting from the first end point

 

Now the y difference in y values must be in the same ratio.

3--4=7

k--4 = k+4

 

\(\frac{k+4}{7}=\frac{2}{3}\\ 3k+12=14\\ 3k=2\\ k=\frac{2}{3} \)

 

 

Melody  Apr 1, 2017
 #2
avatar+302 
+2

Mel, I did'nt understand it. I need it with the formula i've given

SARAHann  Apr 1, 2017
 #4
avatar+90581 
+1

Maybe you understand CPhill's explanation better ?

 

It is good that you said you did not understand.  I appraciate you being honest :))

Melody  Apr 1, 2017
 #3
avatar+76972 
+2

Thanks, Melody.....here's another way....

 

Slope of the line  = [ 3 - - 4 ] / [ - 2 - - 5]  =  7 / 3

 

And the equation of the line is

 

y = ( 7 / 3) (x - -2) + 3  

 

y = (7 / 3) (x + 2) + 3      and when x  = -3, we can find k as

 

k = ( 7 / 3) ( -3 + 2)  + 3

 

k = ( 7 / 3) (-1)  + 3   =   2/3    so.....the point is ( -3, 2/3 )

 

And the ratio is given by

 

[Distance from (-5, -4) to ( - 3 , 2/3) ] /  [ Distance from ( -3, 2/3) to ( -2 , 3) ]

 

Distance from (-5, -4) to (-3, 2/3)   =  sqrt [ ( -3 - - 5)^2 + ( - 4 -2 /3)^2 ]  

sqrt [ 4   + (-14/3)^2 ] =  (2/3)sqrt(58)

 

Distance from ( -3, 2/3) to ( -2 , 3) =  sqrt [ (-2 - - 3)^2 + (3 - 2/3)^2 ]   =

sqrt [ 1  + (7/3)^2 ] = (1/3) sqrt(58) 

 

So......(-3, 2/3)   divides the line in the ratio of :

 

[(2/3)  sqrt (58)] / [ (1/3) sqrt (58) ]   =

 

[2/3] / [ 1/3]  =  2 / 1  =    2 :  1

 

 

 

cool cool cool

CPhill  Apr 1, 2017

19 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details